Causes and Consequences of Indecent Dressing Among Female Students in Oke-Ogun Polytechnic, Oyo State: Implications for School Counselling (Journal of Guidance and Counselling Studies, 2024)
This study examined the causes and consequences of indecent dressing among female students in Oke-Ogun Polytechnic, Oyo state, Nigeria. Simple random sampling technique was used to select three hundred and sixty respondents in school. The instrument used was a researcher-designed scale, titled: “Causes and Consequences of Indecent Dressing Questionnaire (CCIDQ).” The findings of the study revealed that social media influence, lack of moral upbringing, and lack of parental supervision were the major causes of indecent dressing, while the finding also revealed that sexual harassment, low self-esteem and poor school grades were the major consequences of indecent dressing. Further findings showed no significant differences in the causes and consequences of indecent dressing among respondents based on religion. Also a significant difference was showed in the causes of indecent dressing among respondents based on age, while no significant difference was revealed in the consequences of indecent dressing among respondents based on age. It was recommended that school management, in collaboration with school counsellors, should use various media outlets such as television, radio, magazines, newspapers, and handbills to educate female students on the causes and consequences of indecent dressing in school.
Keywords: Causes; Consequences; Indecent dressing; Female students; Oke-Ogun Polytechnic